Anapyrexia during hypoxia - Branco, LGS; Gargaglioni, L. H.; Barros, RCH (Elsevier B.V., 2006)
Reducing body temperature has been found to improve survival not only due to hypoxia (the main focus of this review) but also to ischemia, shock, and many other types of insults. Under these conditions, there is a reduced oxygen delivery to the brain. To compensate the hypoxia, a regulated hypothermia (anapyrexia-Glossary of terms for Thermal Physiology, Commission for Thermal Physiology, 2001) takes place, which has been reported as a beneficial response since the drop in body temperature causes a reduced oxygen demand. The objective of the present article is to review the current knowledge of the mechanisms of hypoxia-induced anapyrexia, focusing on its neurochemical control mainly at the preoptic region of the anterior hypothalamus. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: hypothermia; serotonin; dopamine; nitric oxide